INFLUENCE OF INCREASED BLOOD FLOW ON COGNITIVE IMPROVEMENT: A NARRATIVE REVIEW (CIPEEX, 2025)
Introduction: Mild Cognitive Impairment (MCI) is a decline in cognitive functions such as memory, attention, and language. Effective treatment focuses on correctable causes, such as depression and metabolic diseases. Physical activity plays an important role in brain health, improving memory, cerebral blood perfusion, and promoting new synaptic connections, in addition to increasing cerebral blood flow (CBF) and the supply of oxygen and glucose to specific areas of the cortex. The objective of this literature review is to elucidate the influence of increased CBF on cognitive improvement. Methodology: This literature review was conducted between September 2023 and August 2024, using the MEDLINE/PubMed, Google Scholar, and SciELO databases. Results: CBF is determined by the relationship between blood pressure and cerebrovascular resistance, which is impacted by factors such as blood viscosity and the caliber of cerebral vessels. Nitric oxide (NO), released by endothelial cells in response to increased CO2, plays a crucial role in regulating CBF by promoting vasodilation. The klotho protein regulates its production and is associated with preventing neurodegeneration by protecting endothelial tissue against senescence and apoptosis. Furthermore, platelet factor 4 (PF4) is related to the improvement of the inflammatory response and cognitive function. Physical activity increases the release of neurotransmitters and brain-derived neurotrophic factor (BDNF), promoting angiogenesis and synaptogenesis. Conclusion: Increased CBF has a positive impact on cognition, providing more nutrients to the brain and protecting brain areas involved in memory and learning.
Keywords: Cerebrovascular Circulation; Cognition; Platelet Factor 4; Klotho Protein